2022
DOI: 10.2337/dc21-2601
|View full text |Cite
|
Sign up to set email alerts
|

Projected Impact of the Medicare Part D Senior Savings Model on Diabetes-Related Health and Economic Outcomes Among Insulin Users Covered by Medicare

Abstract: OBJECTIVE The Medicare Part D Senior Savings Model (SSM) took effect on 1 January 2021. In this study we estimated the number of beneficiaries who would benefit from SSM and the long-term health and economic consequences of implementing this new policy. RESEARCH DESIGN AND METHODS Data for Medicare beneficiaries with diabetes treated with insulin were extracted from the 2018 Medical Expenditure Panel Survey. A validated diabe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We have externally validated the BRAVO model against a large number of global diabetes trials and calibrated the model to a nationally representative sample of individuals with type 2 diabetes in the United States 26,27 . The BRAVO simulation model was previously used for several research purposes, including trial simulation, program evaluation and cost‐effectiveness analysis 23,28,29 . Detailed descriptions of the model were well described in a previous paper 24 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have externally validated the BRAVO model against a large number of global diabetes trials and calibrated the model to a nationally representative sample of individuals with type 2 diabetes in the United States 26,27 . The BRAVO simulation model was previously used for several research purposes, including trial simulation, program evaluation and cost‐effectiveness analysis 23,28,29 . Detailed descriptions of the model were well described in a previous paper 24 …”
Section: Methodsmentioning
confidence: 99%
“…26,27 The BRAVO simulation model was previously used for several research purposes, including trial simulation, program evaluation and cost-effectiveness analysis. 23,28,29 Detailed descriptions of the model were well described in a previous paper. 24 We used the BRAVO diabetes model to simulate the 5-year study outcomes for the five study arms, using the SURPASS-2 trial population as the target population.…”
Section: Model Overview and Study Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Rationing of this sort was predicted to increase instances of stroke, myocardial infarction, heart failure, and end-stage renal disease in persons with diabetes. 4 Preventing such rationing by making insulin cheaper could consequently save tens of thousands of quality-adjusted life-years. 3 Current federal proposals-such as capping co-payments for the neediest persons with diabetes-do not reduce the overall prices paid for treatment and therefore may not ultimately be cost-effective.…”
mentioning
confidence: 99%
“…One recent analysis from National Health Interview Survey data found that 1.3 million Americans have rationed insulin in the past year, specifically due to high prices . Rationing of this sort was predicted to increase instances of stroke, myocardial infarction, heart failure, and end-stage renal disease in persons with diabetes . Preventing such rationing by making insulin cheaper could consequently save tens of thousands of quality-adjusted life-years .…”
mentioning
confidence: 99%